Kerangka Konseptual Integritas: Studi Eksplorasi pada Guru-guru Sekolah Dasar di Yogyakarta - Widyarini, Ika; Yuniarti, Kwartarini Wahyu; Nugraha, Leo Aditya (MEDIAPSI, 2019)
Integrity is commitment to positive values i.e. honesty, trust, fairness, respect, responsibility and courage. To encourage children to commit to such positive values, elementary school educatorsare expected to understand the essential values of integrity. This study is an exploratory qualitative study attemptingto buildan understanding on the Indonesian school teacher’s concepts ofintegritywith an indigenous approach. An open ended survey was conducted to a sample of 121 elementary school teachers from Kabupaten Sleman Yogyakarta. A group of elementary school teachers from the sample was recruited to assist the data analysis process, to ensure a data coding in accordance to their conception. The categories were analyzed by descriptive statistics. The result of this research revealed the perspective of elementary school teachers on the importance of certain values involved in integrity, how they teach their students to embrace the values. Theoretical and applied implementation of this research results is discussed.Integritas adalah komitmen terhadap nilai-nilai positif yaitu kejujuran, kepercayaan, keadilan, rasa hormat, tanggung jawab dan keberanian. Untuk mendorong siswa SD berkomitmen pada nilai-nilai positif seperti itu, pendidik sekolah dasar diharapkan memahami nilai-nilai penting dari integritas. Penelitian ini merupakan studi kualitatif eksploratif yang mencoba membangun pemahaman tentang konsep integritas guru sekolah Indonesia dengan pendekatan indijenous. Survei open-ended disebarkan dan diisi 121 guru sekolah dasar dari Kabupaten Sleman Yogyakarta. Kemudian sekelompok guru sekolah dasar dari partisipan tersebut direkrut untuk membantu proses analisis data, untuk memastikan pengkodean data sesuai dengan konsepsi mereka. Kategori dianalisis dengan statistik deskriptif. Hasil penelitian ini mengungkapkan perspektif guru sekolah dasar tentang pentingnya nilai-nilai tertentu yang terlibat dalam integritas dan bagaimana mereka mengajar siswa mereka untuk mengadopsi nilai-nilai luhur. Penerapan teoritis dan praktis dari hasil penelitian ini akan dibahas.